Low literacy skills in adults can be largely explained by basic linguistic and domain-general predictors - Vágvölgyi, Réka; Sahlender, Moritz; Schröter, Hannes; Nagengast, Benjamin; Dresler, Thomas; Schrader, Josef; Nuerk, Hans-Christoph (Frontiers in Psychology, 2024)
Introduction Despite having sufficient formal education, a large group of people cannot complete everyday tasks like reading, writing, or making basic calculations. Regarding reading, millions of people are not able to understand more complex texts despite the ability to read simple words or sentences; they have low literacy skills. Even though this problem has been known for decades, the causes and predictors of their poor reading comprehension skills are not fully explored. Socioeconomic, sociodemographic, and reading-related (i.e., linguistic) factors, especially of English-speaking participants and thus users of an opaque orthography, were often assessed. The goal of this study was to examine which linguistic, domain-general, or numerical factors predict substandard complex text reading as the core symptom of low literacy skills in adulthood. Methods To this end, we assessed a group of German-speaking participants—users of a transparent orthography—who are at risk for complex text reading deficits. Results The results indicated that linguistic variables (reduced word/pseudoword reading, weaker oral semantic and grammatical comprehension), working memory, and age predicted lower performance in text comprehension. This model explained 73% of the total variance, indicating that most of the deficits in complex text reading can be explained by a group of basic underlying linguistic and domain-general factors. Discussion We conclude that interventions for adults with low literacy skills and others at risk for complex text reading deficits should address word/pseudoword reading and focus on both written and oral comprehension.